Maqsud Hifz al-Ummah fi Salat al-Jumu'ah (Dirasah Tahliliyyah min Khilal Haqiqat wa Syurut Salat al-Jumu'ah fi al-Mazahib al-Arba'ah) - Mochamad Baqir, Zaenal Abidin (Fakultas Syariah IAIN Purwokerto, 2020)
Friday Prayer is one of the obligatory services for all Muslims in the world. Aside from being an obligation, Friday prayers are also a gathering place and are a unifying symbol of Muslims. The problem that arises at this time is that many people do not perform Friday prayers; even Friday prayers are held in various mosques in one neighbourhood. This fact denies the essence of Friday prayers. The method used in this paper is a qualitative method with a normative approach. This article aims to find out the purpose of the law (maqÃ„ÂÃ¡Â¹Â£id al-syarÃ„Â«'ah) from the Friday prayers. From the various schools of jurisprudence the four schools can be seen that all the Imams of the schools agreed on the prescribed conditions of Friday prayers and all Muslims must carry them out. The obligation to carry out this Friday prayer, besides aiming at carrying out compulsory worship, is also a gathering place and a symbol of the unity of Muslims. Brotherhood and unity of Muslims can be done if one ward is only held one Friday prayer. This is different from the fact that runs at this time, where many Muslims in one region or neighbourhood perform Friday prayers with more than one mosque. This fact will contradict the intrinsic purpose (al-maqÃ„ÂÃ¡Â¹Â£id al-Ã¡Â¸Â¥aqÃ„Â«qÃ„Â«) of the Friday prayer.